Design and prototyping of an accelerometer based parallel manipulator for endoscope position control - Kalyan Dusarlapudi; Kuthuri Narasimha Raju; Kolusu Kishore Kumar; Kattupalli Sudhakar; Charan Sai Tiruvuri (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The advancement of embedded controllers in minimally invasive robotic surgery (MIRS) provides an innovative and safe alternative to traditional open surgery. This paper illustrates the Accelerometer-based Embedded prototype of 4 link novel parallel manipulator design and endoscope end position control scheme. The parallel manipulator proposed is of 4 leg quadra model with 4 servo actuators to drive the end effector to which endoscope camera integrated with micro electro-mechanical system (MEMS) accelerometer. The parallel manipulator is modeled in Coppeliasim computer-aided design (CAD) and embedded control logic is implemented in the ATmega328P microcontroller. The achieved end effector movement is +/-10cm from the ground clearance validated it in CAD tool. The potentiometer-based position control of the endoscope and its image magnification is recorded. The internet of things (IoT) infrastructure extension to the demonstrated protype is proposed. This cost-effective model is compared with the existed models available in the market.